2004
DOI: 10.1242/jcs.00943
|View full text |Cite
|
Sign up to set email alerts
|

A non-chromosomal factor allows viability ofSchizosaccharomyces pombelacking the essential chaperone calnexin

Abstract: Calnexin is a molecular chaperone playing key roles in protein folding and the quality control of this process in the endoplasmic reticulum. We, and others, have previously demonstrated that cnx1+, the gene encoding the calnexin homologue in Schizosaccharomyces pombe, is essential for viability. We show that a particular cnx1 mutant induces a novel mechanism allowing the survival of S. pombe cells in the absence of calnexin/Cnx1p. Calnexin independence is dominant in diploid cells and is inherited in a non-Men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 36 publications
3
28
2
Order By: Relevance
“…By contrast, the state of naïve cells requiring cnx1 + for viability was renamed Cdn (for calnexin-dependent). Extensive characterization of these calnexin-less cells revealed that the Cin state is mediated by a non-chromosomal element that exhibits prion-like features (Collin et al, 2004). Namely, we showed that the Cin state is stable, is dominant in diploids and in merodiploids harboring a cnx1 + plasmid, and is transmitted in a non-Mendelian fashion.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…By contrast, the state of naïve cells requiring cnx1 + for viability was renamed Cdn (for calnexin-dependent). Extensive characterization of these calnexin-less cells revealed that the Cin state is mediated by a non-chromosomal element that exhibits prion-like features (Collin et al, 2004). Namely, we showed that the Cin state is stable, is dominant in diploids and in merodiploids harboring a cnx1 + plasmid, and is transmitted in a non-Mendelian fashion.…”
Section: Introductionmentioning
confidence: 82%
“…We previously observed that the Cin state induced by the calnexin mutant Δhcd_Cnx1p (Cin Δhcd_cnx1 ) was dominant in diploid cells (Collin et al, 2004), indicating that the Cin Δhcd_cnx1 state stably supersedes the essentiality of calnexin. To further examine the Cin state induced by cif1 + overexpression (Cin cif1 ), Cin cif1 cells were mated to cells that were dependent on calnexin for survival, the Cdn strain (Δcnx1 + pcnx1 + ).…”
Section: Overexpression Of Cif1mentioning
confidence: 99%
See 1 more Smart Citation
“…8,[24][25][26][27][28][29][30] Furthermore, amyloid prepared in vitro from pure recombinant proteins can efficiently transform live cells to the prion state. [9][10][11][12]72,73 Most phenomena associated with prion biogenesis and propagation, including the effects of chaperones 32,[74][75][76] and the existence of strain phenomenon and species barriers 62,[77][78][79][80][81][82] have been modeled in vitro using purified recombinant prionogenic proteins and cellular factors.…”
Section: Prions Facilitate the De Novo Appearance Of Heterologous Prionsmentioning
confidence: 99%
“…10 This once heretical model also appears to be applicable to a number of unrelated phenotypes particularly in fungi, where protein-only models accurately describe the inheritance of a wide range of previously inexplicable phenotypes including the use of alternate nitrogen sources, 11 the regulation of translation termination efficiency, 11 the formation of heterokaryons, 12 the appearance of other prions 13 and organismal dependence on quality control pathways. 14 While appealing, the idea of protein-directed inheritance is at odds with our classical view of genetics. In the simplest case, the transmission of phenotypes from one individual to another either through heredity or infectivity relies on two key events.…”
Section: The Protein-only Mechanismmentioning
confidence: 99%